Thermal Properties, Microstructure and Microhardness of Cu-Al-Co Shape Memory Alloy System - Aydogdu, Yildirim; Kurum, Ferdi; Kok, Mediha; Yakinci, Zehra Deniz; Aydogdu, Ayse (Springer India, 2014)
In this study, the effects of Co content on the crystal structure, transformation temperatures and microstructure of Cu-Al-Co shape memory alloy system were investigated. It was found that Cu-Al-Co alloy system has also 18R type martensitic structure, which is commonly observed in copper-based systems. The transformation temperatures were found to be higher than 250 A degrees C and they do not show a linear increase or decrease with Co content. The microstructural examination revealed the presence of martensite phase and precipitates. It was realized that the size of precipitate increases with increasing Co content. It can be stated that the hardness increased with increasing Co content. All these results point out that increasing Co content increases the strength of Cu-Al-Co shape memory alloy system.
Keywords: Shape memory alloys; Precipitate; Martensite; Vickers hardness